Destabilization in external skeletal fixation finite element method evaluation - Lauer, S. K.; Aron, D. N.; Evans, M. D. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
Destabilization is a concept of pursuing gradual staged disassembly of external skeletal fixators (ESFs) intending to increase only axial loading of the fracture while controlling non-axial loading. The purpose of this study was to determine how destabilization alters loading at the fracture site. The destabilization of a Type III to a Type Ia and Ib ESF was analyzed with the Finite Element Method (FEM) for five callus stages (0%, 0.1%, 10%, 50%, 100% modulus of elasticity of intact bone) for axial compression, torsion, and bending. Axial gap strain (A) comprising the linear displacement along the longitudinal bone axis, the remaining degrees of gap strain (R) comprising all other rotational and linear displacements and the R/A ratio were calculated. In the presence of the callus stages 0% and 0.1%, the R/A ratio ranges between 0.1 and 0.3. Destabilization increases A by two to18 fold and R by five to 41 fold. In the presence of the callus stages 10%, 50% and 100%, the R/A ratio ranges between 1 and 3.2. Destabilization increases A by 2% -15%, and R by 15% -176%. A decrease in the ESF stiffness correlates with an increase of R, A and the R/A ratio. We proposed that the clinical benefits of destabilization might be mechanically based on optimization of the R/A ratio and not of axial strain.
Keywords: External skeletal fixators; FEM; destabilization; axial strain